2014
DOI: 10.1002/2014gl059510
|View full text |Cite
|
Sign up to set email alerts
|

Mean dynamic topography estimates purely based on GOCE gravity field models and altimetry

Abstract: Citation:Becker, S., J. M. Brockmann, and W.-D. Schuh (2014), Mean dynamic topography estimates purely based on GOCE gravity field models and altimetry, Geophys. Res. Lett., 41, 2063Lett., 41, -2069Lett., 41, , doi:10.1002 Abstract The quality of mean dynamic topography (MDT) models derived from an altimetric mean sea surface and a gravity field model mainly depends on the spatial resolution and accuracy of the particular gravity field model. We use an integrated approach which allows for estimating the MDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Several sophisticated approaches to optimal filtering of an altimetric MDT have recently been developed (e.g. Bingham et al 2011;Knudsen et al 2011;Slobbe et al 2012;Becker et al 2014), each of which has pointed to the deficiencies of simple low-pass spatial filtering of the MDT field to reduce noise. However, in the present case we believe that such a simple approach is adequate in describing the MDT's main features.…”
Section: Mdt From Altimetry Minus Geoidmentioning
confidence: 99%
“…Several sophisticated approaches to optimal filtering of an altimetric MDT have recently been developed (e.g. Bingham et al 2011;Knudsen et al 2011;Slobbe et al 2012;Becker et al 2014), each of which has pointed to the deficiencies of simple low-pass spatial filtering of the MDT field to reduce noise. However, in the present case we believe that such a simple approach is adequate in describing the MDT's main features.…”
Section: Mdt From Altimetry Minus Geoidmentioning
confidence: 99%
“…This section summarizes some characteristics of the model and describes comparisons with independent gravity field models. The detailed and specific validation of the model is not part of this paper and will be performed in the future using independent methods and data sets as done for the previous GOCE models by Gruber et al [], Hirt et al [], Rexer et al [], Becker et al [], and Voigt and Denker [].…”
Section: The Solution Egm_tim_rl05mentioning
confidence: 99%
“…In both products, the geostrophic component is obtained by deriving altimeter maps of the ocean absolute dynamic topography, calculated as the sum of the altimeter Sea Level Anomalies (SLA) and an ocean Mean Dynamic Topography (MDT). A number of studies have demonstrated the importance of the recent GOCE (Gravity and Ocean Circulation Experiment) mission for calculating the ocean MDT [ Bingham et al ., ; Knudsen et al ., ; Mulet et al ., ; Becker et al ., ]. The resulting fields are accurate at the centimeter level at scales of around 100–150 km [ Mulet et al ., ], which is a significant improvement over the previous Gravity Recovery and Climate Experiment (GRACE)‐based geoid models.…”
Section: Introductionmentioning
confidence: 99%